(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The most modifying envelope protein is HIV (Env). In this research, we use profound mutational scanning to estimate the effect of all Env amino acid mutations on cell culture viral replication. Most of the mutations are selected for purification in our experiments, while a few locations are selected to enhance the reproduction of HIV in cell culture. We compare the actual frequencies of these amino acids in naturally occurring HIV sequences to our experimental estimates of each site’s preference for each amino acid. Our measured amino acid tastes are mostly matched in natural sequences of amino acid frequencies. Our found biases, on the other side, are less in line with natural amino-acid frequencies at surface-exposed sites that are subject to stresses not present in our tests, such as antibody selection. We test the inherent mutational resistance of each Env site with our results. We show that epitopes of mostly neutralising antibodies are significantly less able to resist mutations, proving a widely held belief. Overall, our findings shed light on how internal functional limitations and external selection pressures shaped Env’s evolution.